Predicting Coastal Vulnerability along Coast of Sampadi - Ahmad Hibbatul Hakimi, Bin Azman (Universiti Malaysia Sarawak (UNIMAS), 2015)
The coasts that bordering South China Sea always experienced one of the monsoons known as Northeast monsoon. During this monsoon, the beaches will subject to erosion greatly. A study was conducted in coast of Sampadi which covers Sampadi beach and also Rambungan beach to predict its vulnerability towards exposure of monsoon period. The study was conducted using Coastal Integrity Vulnerability Assessment Toolkit (CIVAT) as one of the Coral Triangle Initiative Climate Change Adaptations (CTI CCA) toolkits which were done during and post Northeast monsoon. It showed that both of the beaches having erosion but differ during and after NE monsoons. Coastline also shows changes for the past 10 years which is about 48 meter per year for Sampadi beach and about 53 meter per year for Rambungan beach. Vulnerability level for Sampadi coasts were differed according to each beach which is medium vulnerability at Sampadi beach due to medium potential impact and adaptive capacity but high vulnerability at Rambungan beach due to high potential impact and medium adaptive capacity. Awareness levels at Sampadi coast are low as most of the community here are farmers and fishermen with low education backgrounds.